Multifunctional Peri-Urban Agriculture and Local Food Access in the Kathmandu Valley, Nepal: A Review - Shreema, Rana; Rijanta, R.; Rachmawati, Rini (JNRD - Journal of Natural Resources and Development, 2015)
Based on the threatening global challenge of increasing urban population with decreasing resources to feed them, the existing literature is reviewed in this paper to highlight; i) the urban food supply chain, and ii) food security as a benefit of Peri-Urban Agriculture. This is deployed to fit the context of the developing regions of the world where urbanization does not occur in an organized manner. It is known that food grown in peri-urban areas (defined as the fastest growing areas that surround cities but are neither urban nor rural in the conventional sense) is easily available to urban inhabitants. Such peri-urban areas have the least adverse effects on the environment from a food transportation perspective and are more resilient in times of uncertain physical (disaster) and socioeconomic (fuel and food price rise) pressures. Today, much fertile peri-urban land is converted haphazardly without considering its environmental value and agricultural potential. Likewise, peri-urban agriculture is still in the process of being acknowledged by both locals and policy-makers despite being an accepted mode of achieving food security. Therefore, this paper seeks to orient the review literature and underline the gaps that prevail at the grass-roots level of local preferences and values and at the policy-maker level. Using extensive literature review as the methodology, this study draws recent ideas on the multi-functionality of peri-urban agriculture and the sustainable contribution it makes to both developed and developing countries around the world. The findings of the review highlight the significance of peri-urban areas in the Kathmandu Valley for a sustainable and a reliable food chain. It also shows the existing but unrecognized features of peri-urban agriculture both at local and policy-making levels. It discusses the point of interest and possible extension of the multifunctional peri-urban agriculture for local food access, inviting further research to better analyze ways of transition towards sustainable peri-urban agriculture approaches to deal with uncertain food insecurity problems in urban areas.